SIMILARITIES AND DIFFERENCES IN ANTIPLATELET THERAPY IN ACUTE CORONARY SYNDROMES AND ISCHEMIC STROKE - Cichoń, Natalia; Lach, Dominika; Bijak, Michał Bijak; Rzeźnicka, Paulina; Saluk, Joanna (Prospects in Pharmaceutical Sciences, 2016)
Cardiovascular disease, including acute coronary syndromes (ACS) and ischemic stroke (IS), is the most common cause of death in the world. In both ACS and IS, ischemia results from vascular occlusion. Therefore, the mainstay of treatment for these disorders is reperfusion therapy that includes antiplatelet, anticoagulant and thrombolytic interventions. Antithrombotic action (antiplatelet therapy) is the main therapeutic modality in patients with ACS and IS. Its effectiveness depends on the selection of an appropriate pharmacotherapy and on the timing of treatment initiation. The most commonly used drug is acetylsalicylic acid, but the search for new forms of treatment led to the introduction of alternative or supporting pharmaceuticals, including: thienopyridine, prasugrel, ticagrelor, dipyridamole, and glycoprotein IIb/IIIa inhibitors. The aim of this paper is to characterize available drugs and to review modern forms of antiplatelet therapy used in patients with ACS and/or IS.